The impact of wood-derived biochar on the survival of Trichoderma spp. and growth of Secale cereale L. in sandy soil. Issue 4 (3rd April 2018) - Vecstaudza, Dagnija; Grantina-Ievina, Lelde; Makarenkova, Galina; Kasparinskis, Raimonds; Selga, Turs; Steinberga, Vilhelmine; Stelmahere, Solvita; Steiner, Christoph; Muter, Olga
ABSTRACT: The interrelations between biochar (BC) and soil microbiota remain unclear. Addressing this will be important for understanding how BC affects soil properties and plant growth. Here, we tested the influence of wood-derived BC with immobilised Trichoderma viride on rye Secale cereale L. in sandy soil. We found that the addition of BC leads to a significant ( P < .05) increase in the concentrations of Ca 2+ and Mg 2+, as well as a decrease in the concentration of Al 3+, irrespective of BC particle size and the presence of T. viride . Plant growth was stimulated in the presence of small (<2 mm) particle-sized BC. Fungal diversity, as well as an absolute and relative abundance of Trichoderma spp., was tested by cultivation-dependent methods and qPCR. Both of these approaches revealed a positive effect of BC on the survival of Trichoderma spp. under the tested conditions, especially in the presence of a small particle size fraction.